Building Parental Awareness of Children's Education Expenses in the Indonesian Community in Kuala Lumpur, Malaysia - Abdullah Lawang, Karimuddin; Ismail, Diauddin; Erliana, Leni; Subki, Subki; Abdullah Aji, Yunita; Syahrul, Fatahillah (Teumulong: Journal of Community Service, 2024)
Service activities for the Indonesian community taking place at the Kuala Lumpur Indonesian School (SIKL) aim to build Indonesian people's awareness of education in the Indonesian community in Kuala Lumpur, Malaysia. The focus of this activity is the role played by parents in supporting children's education. Through a series of educational outreach activities, such as seminars, workshops and group meetings, efforts are made to increase understanding of the importance of education and the responsibility of parents in maintaining their children's educational costs. The method of implementing activities involves collaboration between SIKL schools, the government and community organizations, with the aim of creating an environment that supports the growth and development of Indonesian diaspora children in Malaysia. It is hoped that the results of this activity can make a positive contribution in strengthening the role of parents in supporting children's education, as well as increasing their access to quality education. Thus, this community service activity is a concrete step in realizing the vision of inclusive and sustainable education for the Indonesian community in Kuala Lumpur.